Ethical judgments of esports spectators regarding cheating in competition. (December 2022) - Johnson, Mark R; Abarbanel, Brett
Esports contests at the highest levels frequently involve millions of dollars in prize money and spectatorship numbers in six or seven figures. Given these opportunities for financial success and public visibility, players have found ways to cheat in esports competitions. We draw on over one thousand qualitative survey responses from esports viewers to examine how spectators perceive cheating, both "cheating to win" (attempting to secure an illegitimate victory) or "cheating to lose" (profit or advancement is secured by throwing a match). We show that spectators hold complex views ranking different forms of cheating, displaying varying levels of understanding of the esports ecosystem, and conceptualising cheating as often more a matter of rule breaking than ethical transgression. We conclude that esports viewers' perspectives are heavily informed by their own play, and the opacity of certain elements of professionalised esports, with implications for the long-term sustainability of esports as a cultural form.